Vicarious motor activation during action perception: beyond correlational evidence - Avenanti, Alessio; Candidi, Matteo; Urgesi, Cosimo (Frontiers in Human Neuroscience, 2013)
Neurophysiological and imaging studies have shown that seeing the actions of other individuals brings about the vicarious activation of motor regions involved in performing the same actions. While this suggests a simulative mechanism mediating the perception of others’ actions, one cannot use such evidence to make inferences about the functional significance of vicarious activations. Indeed, a central aim in social neuroscience is to comprehend how vicarious activations allow the understanding of other people’s behavior, and this requires to use stimulation or lesion methods to establish causal links from brain activity to cognitive functions. In the present work we review studies investigating the effects of transient manipulations of brain activity or stable lesions in the motor system on individuals’ ability to perceive and understand the actions of others. We conclude there is now compelling evidence that neural activity in the motor system is critical for such cognitive ability. More research using causal methods, however, is needed in order to disclose the limits and the conditions under which vicarious activations are required to perceive and understand actions of others as well as their emotions and somatic feelings.